Deoxyribonucleic Acid Extraction Using Iron Oxide Nanoparticle-based Method in Forensic Investigations - Imran Khan; Gaurav Kaushik (Journal of Forensic Science and Medicine)
Extraction of deoxyribonucleic acid (DNA) plays a pivotal role in molecular biology, cell biology, genetic research, and forensic inquiries. In the realm of forensic science, the selection of an efficient DNA extraction method holds utmost importance, as the quality and quantity of isolated DNA significantly influence subsequent applications such as short tandem repeats profiling and restriction fragment length polymorphism analysis. Traditional DNA extraction methods, while being effective, have a number of limitations in terms of yield, quality, and purity of extracted DNA. Addressing these challenges, the nanoparticle-based DNA extraction methods have emerged as a promising alternative to the traditional methods offering a number of advantages over them. This review explores the integration of surface-modified iron oxide nanoparticles in forensic DNA extraction, focusing on their intrinsic properties that are critical to their role in DNA isolation. Polyethyleneimine-functionalized magnetic iron oxide nanoparticles (Fe3O4@PEI) were found to exhibit outstanding DNA adsorption (~99%), magnetization saturation, and thermal stability. However, their effectiveness on dried samples, common in forensic investigations, necessitates further standardization. Despite this limitation, polyethyleneimine-functionalized magnetic iron oxide nanoparticles show great promise and underscore the need for ongoing research to optimize its application in forensic casework.